If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + (x + -10) + 2(x + -10) + 6 = 100 Reorder the terms: x + (-10 + x) + 2(x + -10) + 6 = 100 Remove parenthesis around (-10 + x) x + -10 + x + 2(x + -10) + 6 = 100 Reorder the terms: x + -10 + x + 2(-10 + x) + 6 = 100 x + -10 + x + (-10 * 2 + x * 2) + 6 = 100 x + -10 + x + (-20 + 2x) + 6 = 100 Reorder the terms: -10 + -20 + 6 + x + x + 2x = 100 Combine like terms: -10 + -20 = -30 -30 + 6 + x + x + 2x = 100 Combine like terms: -30 + 6 = -24 -24 + x + x + 2x = 100 Combine like terms: x + x = 2x -24 + 2x + 2x = 100 Combine like terms: 2x + 2x = 4x -24 + 4x = 100 Solving -24 + 4x = 100 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '24' to each side of the equation. -24 + 24 + 4x = 100 + 24 Combine like terms: -24 + 24 = 0 0 + 4x = 100 + 24 4x = 100 + 24 Combine like terms: 100 + 24 = 124 4x = 124 Divide each side by '4'. x = 31 Simplifying x = 31
| 3x^2-5xy+2y^2+3x=0 | | 2.8-5.6= | | 5y-30y+10=-52+2y-4y | | (x^2+x)-6= | | 5*24-3x=90 | | 3k-s=7k-21 | | 5(y+2)=4-7 | | =y-6y^3 | | -(x-1)-3(x+4)=x | | -(x-1)+3(x+4)=x | | 16x+12x=100 | | xy+2x-3y+2+12(x^2)y-3x(y^2)-12x+18y=16 | | 2(x-1)=-(x-3)+(4-x) | | -5.99+23.105x=-587.72x-54.936 | | 36-yi=4x+3i | | (x+2)=-(x-3) | | 5y=11x+6 | | f(x)=2x+3x-1 | | x^2-4x=x(7+x) | | -(x+2)=-(x-3) | | 12m^2-17m-5= | | 15-4x+16=11 | | -6x+15=18x-7 | | 0=-r+6 | | 0=[r+6] | | -(3x+1)=-5 | | a^2-4a+1=0 | | 4X+3-5+2X=20-3X+12 | | x(3x-2)=12x^2-2x-1 | | 9x-16=-205 | | -12x^7-4x^6= | | 7m^2+63m=0 |